Rabies neutralizing antibody detection by indirect immunperoxidase serum neutralization assay performed on chicken embryo related cell line - Cardoso, Tereza Cristina [UNESP]; Silva, Luzia Helena Queiroz da [UNESP]; Albas, Avelino [UNESP]; Ferreira, Helena Lage; Perri, Silvia Helena Venturoli [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2004)
The aim of this study was to evaluate the indirect immunoperoxidase virus neutralization (IPVN) and mouse neutralization test (MNT) to detect antibodies against rabies virus from vaccinated dogs and cattle. The IPVN was set up for the ability to measure 0.5 International Units/ml (IU) of antibody required by the World Health Organization and the Office International des Epizooties as the minimum response for proof of rabies immunization. IPVN was developed and standardized in chicken embryo related (CER) cell line when 141 dog and 110 cattle sera were applied by serial five-fold dilutions (1:5, 1:25, 1:125) as well as the positive and negative reference controls, all added in four adjacent wells, of 96-well microplates. A 50 µl amount of CVS32 strain dilution containing 50-200 TCID50/ml was mixed to each serum dilution, and after 90 min 50 µl of 3 x 10(5) cells/mlcell suspension added to each well. After five days of incubation, the monolayers were fixed and the IPVN test performed. The correlation coefficient between the MNT and IPVN performed in CER cells was r = 0.9949 for dog sera (n = 100) and r = 0.9307 for cattle sera (n = 99), as well as good specificity (94.7%), sensitivity (87.5%), and agreement (96.6%) were also obtained. IPVN technique can adequately identify vaccinated and unvaccinated animals, even from low-responding vaccinated animals, with the advantage of low cost and faster then MNT standard test.
Keywords: rabies virus; neutralizing antibodies detection; chicken embryo related cell; indirect immunoperoxidase assay; mouse neutralization test